Estudio de dosis flexibles de paliperidona ER en pacientes con esquizofrenia previamente tratados sin efectividad con otros antipsicóticos* (2012)
BACKGROUND: Extended-release (ER) paliperidone is an innovative atypical antipsychotic that allows minimal peak-to-through fluctuations with once-daily dosing.OBJECTIVE: To evaluate effectiveness, safety and tolerability of flexible, once-daily doses of paliperidone ER (3-12 mg/day) in patients with schizophrenia from Argentina and Colombia who had previously failed treatment with other antipsychotic agents.METHODS: The authors conducted a 6-month, open-label, prospective and multicentric study. Effectiveness was assessed with Positive and Negative Syndrome Scale (PANSS) and Personal and Social Performance scale (PSP). Other measures of effectiveness, safety and tolerability, were also conducted.RESULTS: Paliperidone ER 3-12 mg/day improved Positive and Negative Syndrome Scale (PANSS) total scores (primary endpoint) from baseline to study end (p < 0,001). In the PANSS total score, the mean change from baseline (83, 9 units) to end point (53,7 units) was significant (p < 0,001). Flexible doses of paliperidone ER demonstrated a ?20% reduction in the PANSS total score (p<0.001) in almost two-thirds of patients. PSP mean change from baseline (52 units) to end point (85 units) was significant (p < 0,001). Secondary effectiveness assessments, as well as safety and tolerability measures, demonstrated favourable results throughout the study.CONCLUSIONS: Flexible doses of paliperidone ER over 6 months were effective, safe and well tolerated in patients with schizophrenia from Argentina and Colombia.